Clinical characteristics of Mycoplasma pneumoniae pneumonia with airway involvement in children - Baoying Zheng; Yuchun Yan; Ling Cao (Pediatric Investigation)
ABSTRACT Importance Mycoplasma pneumoniae pneumonia (MPP) with chest computed tomography (CT) findings showing airway involvement as the main manifestation has begun to be noted and increasingly reported. This type of MPP has different clinical features and may progress to bronchiolitis obliterans (BO). Early recognition and treatment are helpful for reducing sequelae. Objective To investigate the clinical characteristics of MPP patients with airway involvement and provide guidance for clinical recognition of this type. Methods Data from children diagnosed with MPP were collected. Forty‐one patients were assigned to the airway group according to chest CT, and 114 patients were assigned to the air space group. The clinical data of the two groups were compared and analyzed. Results The children in the airway group were younger, and the prevalence of wheezing, pulmonary moist rales, and allergic background in the airway group was greater. The prevalence of severe MPP, the proportions of neutrophils, C‐reactive protein, and D‐dimer were lower in the airway group than in the air space group. Significantly more patients had lung involvement in both airways in the airway group. No cases of BO were found in the airway group. Interpretation Mycoplasma pneumoniae‐associated airway involvement mostly occurs in young children, especially in atopic individuals. Patients with this type of pneumonia are prone to have clinical wheezing and pulmonary moist rales. The airway group included relatively few severe cases, but more patients had involvement of both lungs. Whether the patients in the airway group had a greater chance of developing BO needs further investigation.